Exploring the tensions, pressures and transformations of urban rivers through a social lens : the case study of the Kuils River in the Western Cape, South Africa - Xotyeni, Akhona Lerato (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPhil)--Stellenbosch University, 2022.